Qwen3 vs. Qwen2-1.5B Multilingual Code Generation on HumanEval-X - Assignee Research (Assignee Research, 2026)
This report synthesises findings from 12 peer-reviewed papers addressing the following research question: How does Qwen3's multilingual code generation performance compare to Qwen2-1.5B on the HumanEval-X benchmark across non-English programming languages. 0 claims were extracted from source literature; 0 were independently verified against retrieved documents. An automated multi-reviewer quality assessment produced a score of 6.6/10. This report is a machine-generated literature synthesis and d
Machine-generated literature synthesis.